2016
DOI: 10.1097/qad.0000000000000895
|View full text |Cite
|
Sign up to set email alerts
|

In-utero triple antiretroviral exposure associated with decreased growth among HIV-exposed uninfected infants in Botswana

Abstract: Objective To assess associations between in-utero triple antiretrovirals (cART) versus zidovudine (ZDV) monotherapy exposure and growth among HIV-uninfected children of HIV-infected women in Botswana. Design Secondary retrospective data analysis from two randomized intervention trials of mother-to-child HIV transmission prevention. Methods The Mashi and Mma Bana studies enrolled HIV-infected pregnant women, following their children through 24 months of age. This analysis includes singleton, full-term, HIV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
46
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 18 publications
10
46
2
Order By: Relevance
“…In a previous study we found HEU children exposed to cART in utero had lower length at birth compared with zidovudine monotherapy-exposed children. 30,31 The cross-sectional nature of the study has some limitations but we also note that the children sampled in this survey are likely more representative of the general HEU child population than other studies using secondary analyses of clinical trials and follow-up studies which often provide improved medical care and growth monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study we found HEU children exposed to cART in utero had lower length at birth compared with zidovudine monotherapy-exposed children. 30,31 The cross-sectional nature of the study has some limitations but we also note that the children sampled in this survey are likely more representative of the general HEU child population than other studies using secondary analyses of clinical trials and follow-up studies which often provide improved medical care and growth monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence raises concerns about the safety of certain antiretroviral drugs used in pregnancy, including increased risk for adverse birth outcomes [3,716], problems with pediatric growth and neurodevelopment [17] and future risk of cancer [6, 1820]. Also, HIV-exposed, uninfected (HEU) children have increased morbidity and mortality when compared with HIV unexposed, uninfected (HUU) children.…”
Section: Introductionmentioning
confidence: 99%
“…Most ARVs currently used are considered non-teratogenic; however, short-, medium-, and long-term effects of ARV exposure beyond congenital anomalies are not well understood. Findings from Botswana shared at the workshop indicate that compared to HEU infants with in utero exposure to zidovudine monotherapy, HEU infants with triple ARV in utero exposure had significantly lower length-for-age at 24 months, even after adjusting for maternal disease severity (13). This is just one example of recent findings highlighting the urgent need for large scale pharmacovigilance and ARV safety surveillance that can accommodate the pace of expanding universal ART and inevitably changing regimens.…”
Section: Understanding the Role Of Additional Exposures In Heu Child mentioning
confidence: 99%